Randomised controlled trial of real-time feedback and brief coaching to reduce indoor smoking. Issue 2 (15th February 2019) - Hovell, Melbourne F; Bellettiere, John; Liles, Sandy; Nguyen, Benjamin; Berardi, Vincent; Johnson, Christine; Matt, Georg E; Malone, John; Boman-Davis, Marie C; Quintana, Penelope J E; Obayashi, Saori; Chatfield, Dale; et al.
Abstract : Background: Previous secondhand smoke (SHS) reduction interventions have provided only delayed feedback on reported smoking behaviour, such as coaching, or presenting results from child cotinine assays or air particle counters. Design: This SHS reduction trial assigned families at random to brief coaching and continuous real-time feedback (intervention) or measurement-only (control) groups. Participants: We enrolled 298 families with a resident tobacco smoker and a child under age 14. Intervention: We installed air particle monitors in all homes. For the intervention homes, immediate light and sound feedback was contingent on elevated indoor particle levels, and up to four coaching sessions used prompts and praise contingent on smoking outdoors. Mean intervention duration was 64 days. Measures: The primary outcome was 'particle events' (PEs) which were patterns of air particle concentrations indicative of the occurrence of particle-generating behaviours such as smoking cigarettes or burning candles. Other measures included indoor air nicotine concentrations and participant reports of particle-generating behaviour. Results: PEs were significantly correlated with air nicotine levels (r=0.60) and reported indoor cigarette smoking (r=0.51). Interrupted time-series analyses showed an immediate intervention effect, with reduced PEs the day following intervention initiation. The trajectory of daily PEs over the intervention period declined significantly faster in intervention homes than in control homes. Pretest to post-test, air nicotine levels, cigarette smoking and e-cigarette use decreased more in intervention homes than in control homes. Conclusions: Results suggest that real-time particle feedback and coaching contingencies reduced PEs generated by cigarette smoking and other sources. Trial registration number: NCT01634334 ; Post-results.